Integrating transcriptomics and metabolomics to analyse and target tumour heterogeneity in paediatric ependymoma - Pandele, Alina Gabriela (2024)
Ependymoma (EPN) is the second most malignant paediatric brain tumour which has a five-year survival rate of 25% following relapse. Given the close association between gene expression, active biochemical signalling and metabolism, there is an unmet scientific need to determine whether dysregulated EPN gene expression correlates with aberrant metabolic pathways, which may present therapeutic vulnerabilities. In this context, we present a multi-omics integration at transcriptomic and metabolomics levels.